Analisis intertekstual Roma 9:33 Suatu Pendekatan Memori Semantik Pada Teologi Paulus - Asnita Basir Leman (Predica Verbum: Jurnal Teologi dan Misi, 2023)
Romans 9:33 is known as a very complicated verse with Old Testament intertextual quotations from Isaiah 8:14 and 28:16 in splits and crosses. The use of allusions as key words such as "Zion" and "stone" requires analytical methods and specific rules so as not to be biased in semantic interpretation. Even the change of “disturbed” (Isa 28:16 KJV) to “be ashamed” (Rom 9:33 KJV) has meaning. The inerrancy of the Scriptures can be questioned if it is called just a variation or a scribal error, because there is no scribal doubtness in the textual critics. The research aims to prove Paul's historical canonical semantic intertextual writing technique in Romans 9:33 as a key verse explaining theology justified by faith to the Roman plural congregation. Qualitative research through canonical intertextual analysis is carried out using a semantic historical memory approach through multidisciplinary discourses such as cognitive psychology and architectural archeology. The results of the study show that Romans 9:33 was written using the synchronic multiple contexts semantic memory method which is capable of explaining with precision the theology justified by faith, both to the Jewish and non-Jewish congregations in Rome. The result in this study also provides new afirmation of the dynamics of intertextuality poststructuralism in a canonical context for modern hermeneutics.